The influence of Nav1.9 channels on intestinal hyperpathia and dysmotility - Chenyu Zhao; Xi Zhou; Xiaoliu Shi (Taylor & Francis Group, 2023)
ABSTRACTThe Nav1.9 channel is a voltage-gated sodium channel. It plays a vital role in the generation of pain and the formation of neuronal hyperexcitability after inflammation. It is highly expressed in small diameter neurons of dorsal root ganglions and Dogiel II neurons in enteric nervous system. The small diameter neurons in dorsal root ganglions are the primary sensory neurons of pain conduction. Nav1.9 channels also participate in regulating intestinal motility. Functional enhancements of Nav1.9 channels to a certain extent lead to hyperexcitability of small diameter dorsal root ganglion neurons. The hyperexcitability of the neurons can cause visceral hyperalgesia. Intestinofugal afferent neurons and intrinsic primary afferent neurons in enteric nervous system belong to Dogiel type II neurons. Their excitability can also be regulated by Nav1.9 channels. The hyperexcitability of intestinofugal afferent neurons abnormally activate entero-enteric inhibitory reflexes. The hyperexcitability of intrinsic primary afferent neurons disturb peristaltic waves by abnormally activating peristaltic reflexes. This review discusses the role of Nav1.9 channels in intestinal hyperpathia and dysmotility.